2000
DOI: 10.1016/s0022-2275(20)32399-3
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and vessel wall lipoprotein lipase have different roles in atherosclerosis

Abstract: Lipoprotein lipase (LPL) is a key enzyme in lipoprotein metabolism, and has been hypothesized to exert either pro-or anti-atherogenic effects, depending on its localization. Decreased plasma LPL activity is associated with the high triglyceride (TG)-low HDL phenotype that is often observed in patients with premature vascular disease. In contrast, in the vessel wall, decreased LPL may be associated with less lipoprotein retention due to many potential mechanisms and, therefore, decreased foam cell formation. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(12 citation statements)
references
References 59 publications
0
10
0
2
Order By: Relevance
“…39,40 LpL activation in the muscle and adipose tissue plays an anti-atherogenic role due to a decrease in plasma triglycerides and increased HDL. 41,42 We have found that CIH induces a striking 5-fold decrease in the adipose LpL activity. Our previous work has shown that CIH leads not only to loss of epididymal fat, but also to hepatic steatosis.…”
Section: Discussionmentioning
confidence: 84%
“…39,40 LpL activation in the muscle and adipose tissue plays an anti-atherogenic role due to a decrease in plasma triglycerides and increased HDL. 41,42 We have found that CIH induces a striking 5-fold decrease in the adipose LpL activity. Our previous work has shown that CIH leads not only to loss of epididymal fat, but also to hepatic steatosis.…”
Section: Discussionmentioning
confidence: 84%
“…LPL expression is regulated by a variety of physiological and pathophysiological stimulations. It has been discovered that LPL mRNA levels are increased in macrophage-derived foam cells in atherosclerotic lesions ( Yla-Herttuala et al., 1991 ) and LPL protein expression in arterial atherosclerotic plaques is associated with progression of atherosclerotic lesions ( Clee et al., 2000 , Takahashi et al., 2008 , Wilson et al., 2001 ), suggesting that LPL may be pro-atherogenic. Our results from systemic MCPIP1 knockout mice, including the reduced HDL-cholesterol and increased LDL/VLDL-cholesterol, support the hypothesis that the upregulation of LPL may be associated with increased risk of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…It is anchored to the vascular endothelium where it constitutes the rate-limiting step in the catabolism of triglycerides in circulating triglyceride-rich lipoproteins [59,60]. The contribution of lipoprotein lipase to atherogenesis is significantly influenced by the balance between vessel wall protein (pro-atherogenic) and plasma activity (anti-atherogenic) [61].…”
Section: Mutations In the Lipoprotein Lipase Genementioning
confidence: 99%